If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -2) = 5x + 5 + -3(-3x + -2) Reorder the terms: 2(-2 + x) = 5x + 5 + -3(-3x + -2) (-2 * 2 + x * 2) = 5x + 5 + -3(-3x + -2) (-4 + 2x) = 5x + 5 + -3(-3x + -2) Reorder the terms: -4 + 2x = 5x + 5 + -3(-2 + -3x) -4 + 2x = 5x + 5 + (-2 * -3 + -3x * -3) -4 + 2x = 5x + 5 + (6 + 9x) Reorder the terms: -4 + 2x = 5 + 6 + 5x + 9x Combine like terms: 5 + 6 = 11 -4 + 2x = 11 + 5x + 9x Combine like terms: 5x + 9x = 14x -4 + 2x = 11 + 14x Solving -4 + 2x = 11 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. -4 + 2x + -14x = 11 + 14x + -14x Combine like terms: 2x + -14x = -12x -4 + -12x = 11 + 14x + -14x Combine like terms: 14x + -14x = 0 -4 + -12x = 11 + 0 -4 + -12x = 11 Add '4' to each side of the equation. -4 + 4 + -12x = 11 + 4 Combine like terms: -4 + 4 = 0 0 + -12x = 11 + 4 -12x = 11 + 4 Combine like terms: 11 + 4 = 15 -12x = 15 Divide each side by '-12'. x = -1.25 Simplifying x = -1.25
| 6=j | | 9(0)-3y=-81 | | 6+3*6+6= | | 3+3*6+6= | | 0.2y=1600-8400 | | x^2-24x+27=0 | | 0.2y=8400-1600 | | 3x-24=1x+10 | | 9x-3(0)=-81 | | 8w^2+2w-1=0 | | 2+2p=6 | | 168/x=12 | | 9x-3y=-81 | | 3h^2+10h-8=0 | | n-15=31 | | 104=2v^2+8 | | x+5=4x-13 | | 12=2L+(10) | | 56=w^2+6 | | 0.25x+0.2y=350 | | 988()=1234 | | x(x+5)=-150 | | x+7=3-x | | 2y+2+10y-2=90 | | 1Dwight+2x= | | 3(m-3)=0 | | 7m-2=0 | | 11x-5x+6x=168 | | -73+29= | | 2x+11=3x+11 | | 7ab(a+5b+ab-6^2)= | | 6z+18=z |